2004
DOI: 10.1097/01.ede.0000101023.41844.ac
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Air Pollution and Fetal Health

Abstract: The currently available evidence is compatible with either a small adverse effect of particulate air pollution on fetal growth and duration of pregnancy or with no effect. Further research should be directed toward clarifying and quantifying these possible effects and generating testable hypotheses on plausible biologic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
127
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 322 publications
(130 citation statements)
references
References 38 publications
0
127
1
2
Order By: Relevance
“…We identified relevant publications using database searches with a comprehensive list of search terms and other established search methods (for details, see Glinianaia et al 2004). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified relevant publications using database searches with a comprehensive list of search terms and other established search methods (for details, see Glinianaia et al 2004). …”
Section: Methodsmentioning
confidence: 99%
“…We undertook a systematic review to summarize the epidemiologic evidence for an association between levels of particulate air pollution and infant outcomes. This work was part of a broader systematic review of the association between ambient air pollution and fetal (Glinianaia et al 2004) and infant health outcomes.…”
mentioning
confidence: 99%
“…PM10 also has a direct effect on health via inhalation [5]. Glinianaia et al [17] and Šrám et al [18] have reported the effects of particulate matter on infant birth weight. Samet et al [19] found that an elevated PM10 concentration can increase mortality rates the following day.…”
Section: Introductionmentioning
confidence: 99%
“…Our article followed on from many other studies reporting associations between atmospheric pollution levels and pregnancy outcomes, the earliest of which was published more than 30 years ago (Williams et al 1977). These studies have been the subject of several reviews (Glinianaia et al 2004;Lacasana et al 2005;Maisonet et al 2004;Ritz and Wilhelm 2008;Slama et al 2008;Sram et al 2005) and have led the WHO to conclude that, "There is evidence that implicates ambient air pollution in adverse eVects on pregnancy, birth outcomes and male fertility." (Krzyzanowski et al 2005).…”
mentioning
confidence: 95%